Fatwa MUI Nomor 4 Tahun 2003 Tentang Penggunaan Nama Kuliner Unik Perspektif Fikih - Muhammad Arfan Ahwadzy (AL-BAYAN INSTITUTE, 2024)
The uniqueness of culinary names in restaurants or eateries has led some of these names to carry negative connotations in the eyes of certain segments of society. Many culinary names, such as